Enhancing PEEK bond strength: the impact of chemical and mechanical surface modifications on surface characteristics and phase transformation - Emel Arslan; Ipek Caglar (BMC Oral Health)
Abstract Objectives This study investigated the effects of different surface modifications on surface roughness, phase transformation, and bond strength of polyetheretherketone (PEEK) to composite resin. Materials and Methods A total of 140 specimens measuring 10 mm × 10 mm × 2 mm were fabricated from PEEK blocks (BioHPP; Bredent GmbH & Co KG, Germany). Seven groups were randomly formed from the specimens: C) untreated control group, (SE) sulfuric acid application (Merck KGa, Darmstadt, Germany), (PE) piranha solution application (Albar Chemistry, Kocaeli, Turkey), (S) sandblasting with Al2O3 particle (Zhermack, Rovigo, Italy), (T) tribochemical silica coating (3 M ESPE, Seefeld, Germany), (L) Er-YAG laser treatment (LightWalker AT, Fotona, Slovenia), and (P) plasma treatment (Kinpen, Neoplas, Germany) (n = 20). Surface topography was examined using a profilometer device (Taylor Hobson, Leicester, England). Surface images of the specimens were captured using Scanning Electron Microscopy (SEM) (JSM- 6610, Jeol, USA). Phase change analysis was conducted on each group using an X-Ray Diffractometer device (Rigaku SmartLab Diffraktometer, Tokyo, Japan). After thermal aging, shear bond strength was tested using a Universal Test Machine (Model 3340, Instron Corp., Wycombe, UK). Data were analyzed with One-way analysis of variance (ANOVA) test; comparisons were made with Tukey's multiple comparison test, with a significance level of 0.05. Results Group S (3.09 ± 0.40 μm) exhibited significantly higher surface roughness values compared to the other groups (p < 0.05). Group SE (13.28 ± 1.69 MPa) exhibited significantly higher shear bond strength values than the other groups (p < 0.05). No statistically significant correlation was found between surface roughness and bond strength data (p > 0.05). According to XRD results, Group S and Group L differ from the other groups in having a slightly higher intensity and broader peaks. Conclusions All surface modification methods enhanced the bond strength between PEEK to composite resin. However, Group L and Group S revealed different XRD patterns from the control group. Tribochemical silica coating can be a reliable alternative method for acid applications due to its stable phase structure and high bond strength.